Gender sensitivity level of the municipal PNP Women's Desks in the Province of Antique its implications on the functions and accomplishments of the office - Del Rosario, Jo-an Calumno
This is an exploratory study of gender-sensitivity level of the personnel of the PNP Wmen's Desk in the Province of Antique. This study utilized self-administered questionnaires and unstructured interview schedules. The respondents of the study were composed of the personnel of the PNP Women's Desks in the twelve selected municipalities of Antique namely: Sebaste, Culasi, Tibiao, Barbaza, Laua-an, Valderama, San Remegio, Sibalom, San Jose, Hamtic, Tobias Fornier and Anini-y. another set of respondents was taken from local government agencies that were tasked to assess the PNP Women's Desks personnel. some civilians were also tested of their level of awareness about the PNP Women'sDesk., As validity test, the study utilized Pearson Product Moment Correlation Coefficient in measuring the relationship between the independent and dependent variables in the study. The study found out that socio-economic factors such as age, income, educational attainment, religion and length of service did not affect the gender-sensitivity level of the PNP Women's Desk Officer. Although preliminary findings of the study showed that a younger population exhibits high gender-sensitivity, the Product Moment Correlation Coefficient proved it otherwise. Membership in gender-related organizations on the other hand, seemed to affect the gender-sensitivity level of the PNP Women's Desk Officer. Gender sensitivity of the PNP Women's Desk Officer in general, seemed to affect the effectivity of the office. Aside from gender-sensitivity, the socio-economic statusof the locality, information dissemination campaigns of gender-related issues conducted in the community and alliances with other government agencies affect the effectivity of the office. It was found out in the study that the civilian population were generally unaware of the PNP Women's Desk and there is a need for further information dissemination campaigns regarding gender-related issues and the role of PNP Women's Desk in the communities. A number of actions to promote its effectivity should also be undertaken. In general, the study found out that the PNP Women's Desks in the Province of Antique is ineffective due to a number of factors that were raised by the findings of the study.